1959
DOI: 10.1107/s0365110x59000135
|View full text |Cite
|
Sign up to set email alerts
|

Ternary semiconducting compounds with sodium chloride-like structure: AgSbSe2, AgSbTe2, AgBiS2, AgBiSe2

Abstract: The high temperature modification of AgSbS%, AgSbTe 2, AgBiS~, and AgBiSe2 has a face-centered cubic statistically NaCl-type structure with Ag and Bi (or Sb) atoms distributed indistinguishably and on the average in one set of positions (0, 0, 0; 0, ½, ½; O) and the Group VI atoms distributed on the average in the other set of positions (½, ½, ½; 0, 0, ½; ~). Because it is extremely unlikely that the Ag, Bi and Sb atoms all have the same effective sizes in these compounds, at least one group of atoms (4(a) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
129
1
2

Year Published

1993
1993
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(152 citation statements)
references
References 0 publications
8
129
1
2
Order By: Relevance
“…7 They assumed that single crystals prepared by them had rock salt structure (Fm 3m), with Ag and Sb atoms distributed statistically in one of the Wyckoff positions (4a) and Te atoms occupying the second one (4b). Geller and Wernick observed that the nature of the disorder should be complicated because both type of atoms: Ag and Sb differ significantly in electronic structure, atomic radius, and other chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…7 They assumed that single crystals prepared by them had rock salt structure (Fm 3m), with Ag and Sb atoms distributed statistically in one of the Wyckoff positions (4a) and Te atoms occupying the second one (4b). Geller and Wernick observed that the nature of the disorder should be complicated because both type of atoms: Ag and Sb differ significantly in electronic structure, atomic radius, and other chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical component of the second phase is the same as bulk AgSbTe 2 . 19 In this model there are no Pb atoms inside the minor phase. For the minor phase of this model we tried both a chemically disordered cluster model N C0 0 with a cubic unit cell and Ag, Sb atoms distributed randomly on the lead sublattice ( Fig.…”
Section: Modelingmentioning
confidence: 99%
“…This high-temperature polymorph survives metastably at room temperature. Low-temperature matildite, 13-AgBiS2, is hexagonal (Geller and Wernick, 1959), while the hightemperature cubic form (confusingly called ~-AgBiS2) exists above 210~ (Hofmann, 1938;Graham, 1951). Hall (1966) synthesized three polymorphs of AgAsS2; below 320~ the rhombohedral mineral trechmannite, 7-AgAsS2, is stable Mineralogical Magazine, June 1996, Vol.…”
Section: Introductionmentioning
confidence: 99%
“…60, pp. 393-401 C~ Copyright the Mineralogical Society References: 1, tlofmann (1938); 2, Graham (1951); 3, Knowles (1964): 4, Keighin and Honea (1969); 5, Geller and Wernick (1959);6, Hall (1966);7, Roland (1968); 8, Matsumoto and Norwacki (1968).…”
Section: Introductionmentioning
confidence: 99%